Life of Things from the Perspective of Polish Systemic Transformation - Dopierała, Renata (Qualitative Sociology Review, 2019)
The main purpose of the paper is to present the “biography” of selected things which appear in autobiographical narrative interviews conducted within the project “Experiencing the Systemic Transformation Process in Poland. A Sociological Comparison on the Basis of Biographical Analysis.” The author discusses different social actions connected with things, for example, the migrations of things, emancipation through things, collecting things, and reconstructs the stages of life of such things as: notebooks, cassette, and video tapes. The considerations are mainly embedded in the context of the People’s Republic of Poland and the process of transformation of the 1990s. The sociology and anthropology of things are theoretical frames of the analysis.